2022
DOI: 10.1111/ntwe.12256
|View full text |Cite
|
Sign up to set email alerts
|

Skilled maintenance trades under lean manufacturing: Evidence from the car industry

Abstract: This article explores how skilled maintenance trades have fared under lean automotive manufacturing, a cohort of workers relatively neglected in the literature. Historically, such trades possessed a distinct 'craft consciousness' derived from apprenticed-acquired skill, autonomy in job execution, strict job boundaries and relative occupational status and prestige. The article assesses how lean has impacted this craft tradition over time, drawing on a case study of one UK car plant to assess its trajectory acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Our study examined only general skills and future research could examine both specific and general skills comparing distinctive occupational, organizational and industry contexts (Roberts and Cullinane, 2023). Zenner-Höffkes et al (2021) found in survey studies on employability that employers rate soft skills more highly than do graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Our study examined only general skills and future research could examine both specific and general skills comparing distinctive occupational, organizational and industry contexts (Roberts and Cullinane, 2023). Zenner-Höffkes et al (2021) found in survey studies on employability that employers rate soft skills more highly than do graduates.…”
Section: Discussionmentioning
confidence: 99%